Utilization of Tofu Liquid Waste on the Abundance of Microalgae Spirulina sp. In the Open Space - Dahlila Hidayani; M Hasbi M Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract             Tofu liquid waste contains a lot of organic matter that can be used as good nutrients for the growth of Spirulina sp. The purpose of this study was to determine the benefits of tofu liquid waste for the growth process of Spirulina sp. optimally. In addition, this study was also conducted to find the best concentration of tofu liquid waste for the growth of Spirulina sp. carried out in the open. This research was conducted in June-July 2021 with 5 different types of treatment, namely P0, P1(20%), P2(40%), P3(60%) and P4(80%) using a Completely Randomized Design (CRD) method with 3 repetition times. The volume of each experimental unit was 3 liters and 100 ml of Spirulina sp seeds were added to each unit. Then cultured for 10 days. Parameters measured in this study were abundance, biomass, nitrate, phosphate, dissolved oxygen, pH and temperature. The highest abundance results were found in treatment P3(2862 × 103cells/ml) on day 8 and the lowest was in treatment P0(304 × 103cells/ml) on day 1. The highest biomass of Spirulina sp. It was found in the P3treatment (0.51 g/l) and the lowest was in treatment P0(0.07 g/l). Based on the data obtained, it can be concluded that distilled water can be enriched by the addition of tofu liquid waste fermentation as an alternative nutrient for the growth of Spirulina sp. Keywords: Liquid waste, nutrients, algae culture, microalgae Spirulina sp